The internalization of akhlaq among Selangor secondary school students - Abdul Razak, Khadijah; Ismail, Habsah (Canadian Center of Science and Education, 2013)
The internalization of akhlaq is vital as it serves as a stronghold that preserves one’s belief, values, faith and culture. This will make one not only knowledgeable but also practices his belief in all aspects of his life. The question is whether or not today’s education is internalizing akhlaq among the students? This paper discusses the findings of a study on the internalization of akhlaq among secondary school students in the state of Selangor, Malaysia. This quantitative study involved 715 form four Muslim students aged 16 years old from 10 secondary schools in Selangor. A questionnaire was employed in collecting the data. It consisted of three constructs to measure the internalization of akhlaq, i.e. akhlaq towards Allah, the Prophet, and the Qur'an. The findings showed that the respondents could be classified into two levels of internalization of akhlaq, i.e. high level and moderate. The high internalization of akhlaq was towards Allah; while the moderate internalization of akhlaq was towards The Prophet, and the Quran. However, the overall findings showed a moderate level of internalization of akhlaq among the respondents. The finding also showed significant differences in the internalization of akhlaq based on gender and school location.